Durana, Albania: A Field of Possibilities. (July 2016) - Fabi, Ambra; Piovene, Giovanni
Abstract : Durana is a disjointed metropolitan area that sprang up between Albania's two main cities Tirana and Durrës after the fall of communism. A government‐run competition in late 2014 sought ideas for improvements to public space in the region. Here, Ambra Fabi andGiovanni Piovene of PIOVENEF ABI – part of a multidisciplinary team that supplied one of the winning proposals – set out their vision, which works at multiple scales from masterplanning to individual architectural interventions.